Angiographic Anatomy of Abdomenopelvic Organs - Penprapa Klinkhachorn; Powsiri Klinkhachorn; Robert Tallaksen; Patricia Stoltzfus; Daniel Slaon; Frank Reilly (Association of American Medical Colleges, 2011)
Abstract Introduction This interactive tutorial serves as an introduction to normal vascular anatomy of abdominopelvic organs for preclinical medical students. It is composed of high-quality digital subtraction angiography and surface-rendered CTs containing comprehensive labeling of blood vessels. Image resolution exceeds that found in many more conventional learning resources such as textbooks, dissectors, and atlases. Images were digitized and converted into Macromedia Flash to stimulate self-directed learning by integrating introductory angiography into a structured format that is readily accessible for local and distance learning. Methods Active learning was achieved by providing learners with opportunities for repetition and self-assessment through immediate feedback and quizzes on labeled structures. The tutorial is best used in conjunction with radiology/anatomy lectures and labs to reinforce the didactic and practical (dissection) experiences for learners enrolled in human anatomy courses. Results In 2007 to 2009, learners scored between 63rd to 77th percentiles on the gross anatomy subject examination. These scores are significantly higher than those recorded prior to implementation of instructional technology into the curriculum beginning in 2001. Discussion The major limitation is that the courseware deals only with normal vascular anatomy. This is appropriate for pre-professional learners. However, to take the tutorial to the next level for residents and showcasing imaging techniques will require inclusion of pathological specimens of vascular aberrations and anomalies.